Language issue in the 21st century and the centuries ahead: an exercise in crystal-ball gazing - Rajagopalan, Kanavillil (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
Written in a speculative spirit, this paper is an attempt to take a peek into what the future might hold for the study of language. It takes into account the phenomenal changes that the world has undergone since the days when modern linguistics constituted itself as an academic discipline. It is argued that these changes call for a radical rethinking of some of the fundamental assumptions about language that have hardly ever been questioned until now